2023
DOI: 10.1136/bmjopen-2023-074631
|View full text |Cite
|
Sign up to set email alerts
|

Protocol for a 2-year longitudinal study of eating disturbances, mental health problems and overuse injuries in rock climbers (CLIMB)

Klara Edlund,
Isabel Nigicser,
Mikael Sansone
et al.

Abstract: IntroductionRock climbing is a rapidly growing sport in which performance may be affected by participant’s weight and leanness, and there may be pressure on athletes with respect to their eating behaviour and body weight. However, there is sparse research performed on climbers, constituting a knowledge gap which the present study aims to fill. The primary outcomes of the study are to examine disordered eating and overuse injuries in rock climbers. Secondary variables are body image, indicators of relative ener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Based on previous retrospective data from rock-climbers, using a power of 80%, a significance level of 5%, and an expected relative risk of 1.5 for the primary outcome, we calculated that at least 55 participants were needed in each group (rock-climbers and control group) [ 13 ]. The study constitutes a baseline measurement, as part of a larger longitudinal study, with pre-registered procotol in BMJ OPEN, where a more detailed description of the study methodology can be found [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous retrospective data from rock-climbers, using a power of 80%, a significance level of 5%, and an expected relative risk of 1.5 for the primary outcome, we calculated that at least 55 participants were needed in each group (rock-climbers and control group) [ 13 ]. The study constitutes a baseline measurement, as part of a larger longitudinal study, with pre-registered procotol in BMJ OPEN, where a more detailed description of the study methodology can be found [ 14 ].…”
Section: Methodsmentioning
confidence: 99%